2020
DOI: 10.1177/2325967120968552
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation and Validation of the Oslo Sports Trauma Research Center Questionnaires on Overuse Injury and Health Problems (2nd Version) in Spanish Youth Sports

Abstract: Background: The Oslo Sports Trauma Research Center Questionnaires on Health Problems (OSTRC-H) and Overuse Injury (OSTRC-O) have shown a greater ability to identify athletes with health problems and to estimate the severity of those problems compared with traditional surveillance methods. Despite the numerous language adaptations of these questionnaires and their extended use, some of their measurement properties remain unknown. Moreover, these questionnaires are not available for Spanish-speaking athletes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 35 publications
(108 reference statements)
3
18
0
Order By: Relevance
“…Although previous studies have demonstrated that the questionnaire is a valid and reliable tool [ 7 , 8 , 11 13 ], when adapting the questionnaire to contexts beyond adult sports, such as adolescent football, the wording needs to be adjusted and new psychometric testing and validation should be performed [ 15 ]. In alignment with other studies [ 10 12 ], we ensured feasibility through our pretest and the final questions about comprehensibility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although previous studies have demonstrated that the questionnaire is a valid and reliable tool [ 7 , 8 , 11 13 ], when adapting the questionnaire to contexts beyond adult sports, such as adolescent football, the wording needs to be adjusted and new psychometric testing and validation should be performed [ 15 ]. In alignment with other studies [ 10 12 ], we ensured feasibility through our pretest and the final questions about comprehensibility.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaires have been developed to identify and record different types of health complaints including illness and injuries, and to quantify the effect these have on sport participation [ 8 , 9 ]. Several studies have explored the psychometric properties of the questionnaires across different contexts and populations [ 7 , 10 14 ], confirming that the questionnaires are valid and reliable tools. Additionally, a range of elite sport organizations have employed the tools in their sport injury research and clinical health monitoring programmes [ 15 ].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations